2015
DOI: 10.1111/lang.12091
|View full text |Cite
|
Sign up to set email alerts
|

Processing Determinism

Abstract: I propose that the course of development in first and second language acquisition is shaped by two types of processing pressures—internal efficiency‐related factors relevant to easing the burden on working memory and external input‐related factors such as frequency of occurrence. In an attempt to document the role of internal factors, I consider a series of case studies involving contrasts that are rarely instantiated in the input, yet show early mastery. I conclude with some general remarks about the nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 71 publications
1
39
0
Order By: Relevance
“…It is thus plausible that the children's more restricted cognitive resources led to overly schematic linearization patterns and restricted any attempt to work on the internal structure of phrases or words. This interpretation would be compatible with the idea of processing determinism and its claim that “low processing cost is a powerful attractor state” (O'Grady, , p. 26). It is also possible that children are generally less creative L2 users and as faithful to the input as possible under the given circumstances.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It is thus plausible that the children's more restricted cognitive resources led to overly schematic linearization patterns and restricted any attempt to work on the internal structure of phrases or words. This interpretation would be compatible with the idea of processing determinism and its claim that “low processing cost is a powerful attractor state” (O'Grady, , p. 26). It is also possible that children are generally less creative L2 users and as faithful to the input as possible under the given circumstances.…”
Section: Discussionsupporting
confidence: 64%
“…In a study of untutored acquisition of preverbal negation in L2 Italian, Bernini (, p. 432) concluded that “[p]reposition of the negator to the verb [is] a nonmarked structure in typological terms and [that] scope domain on the right in both clause and constituent negation may be the major factors effecting ease of acquisition.” If one accepts the idea that learners’ default assumption about negation corresponds to a typologically unmarked structure in which the negation operator precedes the negated elements (VP) on the surface, the uniform behavior of the German learners of Polish can be explained along the same lines. It is the comparison of the two types of target grammars (initial stages in the acquisition of German/French vs. Polish/Italian) that suggests that some internal pragmatic constraints and/or ease‐of‐processing constraints (O'Grady, ) play an important role. This is reinforced by the limited input frequency of negation that we can precisely determine in the current data set.…”
Section: Resultsmentioning
confidence: 99%
“…Some theorists argue for an even stronger, causal relation between online processing and learning (e.g. O'Grady, 2005O'Grady, , 2015; see Phillips & Ehrenhofer, 2015). That is, online processing may be a mechanism by which learning is driven and constrained, and processing difficulty (e.g.…”
Section: Online Effects Of Ei and Practicementioning
confidence: 99%
“…If learners tend to rely on L1 English processing routines they would not reliably use morphological information in the discourse to disambiguate past habituality from ongoingness (which arguably demands more processing resources than immediate disambiguation within the verb phrase (O'Grady, 2005(O'Grady, , 2015). This could result in nonoptimum (less accurate and slower) interpretations of IMP.…”
Section: A Potential Testing Ground For Instruction In a Cross-linguimentioning
confidence: 99%
“…Rothman and Slabakova () have recently argued that the bulk of linguistic properties is acquired based on the evidence of the linguistic input, or primary linguistic data (to be discussed at length in the next section) and may well take the route described by the usage‐based paradigm. In addition, O'Grady's () processing determinism is an elaborate emergentist framework that offers a middle ground between some‐innate‐knowledge and all‐usage descriptions of language development. In this approach, processing costs determine which morphosyntactic operations place a lower burden on working memory, prompting languages and learners to favor them over other, more costly derivations.…”
Section: Where Are Gensla Approaches Situated?mentioning
confidence: 99%